Electrophototherapeutic Resources Associated or Not With Exercise and Dosimetry Used in Subacromial Impingement Syndrome: A Scoping Review - Kauanny Lopes Pereira; Renata Anddresa Stacheslki; Alberito Rodrigo de Carvalho; Gladson Ricardo Flor Bertolini; Márcia Rosângela Buzanello (Physical Therapy Korea)
Background: Electrophototherapeutic resources are widely used in the treatment of shoulder injuries, despite some contradictory results. Objects: This scoping review aims to evaluate the existing electrophysical resources associated or not with physical exercise (EX), propose a dosage and to evaluate the methodological quality, for managing pain, range, and muscle strength in patients with subacromial impingement syndrome (SIS). Methods: Randomized clinical trials (RCTs), non-RCTs (NRCTs) and systematic reviews of electrophototherapeutic interventions in people with SIS were included, with no restrictions on age, sex, year or language. The outcomes were pain intensity, range of motion, and muscle strength. The databases searched were PubMed, Scopus, Embase, Cochrane, Web of Science, LILACS, PEDro, Google Scholar, Open Grey, LIVIVO, CAPES Catalogue of Theses and Dissertations, and citation search. The search was carried out on January 26, 2023 and updated on March 5, 2024. The risk of bias of the included studies was assessed individually using the Cochrane risk of bias tools for randomized trials (RoB 2) and for non-randomized trials (ROBINS-I) and the AMSTAR-2 tools for systematic review studies. Results: Twenty studies were included (14 RCTs, one NRCT, and 5 review studies). The electrophototherapeutic resources used were photobiomodulation, high-intensity laser therapy (HILT), laser associated with light-emitting diode, Multiwave Locked System laser, extracorporeal shockwaves (ESWs), low-frequency electrical current stimulation, therapeutic ultrasound and radiotherapy. Ten clinical studies applied EX in their intervention, in addition to electrophototherapeutic resources. Conclusion: Photobiomodulation, HILT and ESWs have been shown to be effective in treating SIS, however, there was great heterogeneity in the quality of the studies included, with some risks of bias. The additional effects of electrophototherapeutic resources to EX for patients at different stages of SIS are still uncertain, and the dosimetric parameters were presented in tables in the text.